2016
DOI: 10.1055/s-0042-106301
|View full text |Cite
|
Sign up to set email alerts
|

Wearing Compression Garment after Endurance Exercise Promotes Recovery of Exercise Performance

Abstract: The present study examined the effects of wearing a lower-body compression garment (CG) after endurance exercise on recovery of physiological function. 18 males were divided into 2 experiments, the downhill running (n=10, DHR) experiments and the level running (n=8, LR) experiments. Subjects performed 30 min of DHR (gradient: - 10%) or LR (gradient: 0%) at 70% of  ˙VO2max with either wearing a CG (CG trial) or normal garment (CON trial) for 24 h after running. Changes in jump performance (counter movement jump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 35 publications
(51 reference statements)
4
34
0
2
Order By: Relevance
“…Therefore, the acute increases in leg stiffness associated with a lower relative time spent in contact with the ground can be interpreted as a more dynamical running pattern and leg mechanical behavior. Previous studies have suggested such biomechanical improvements may reside in the ergogenic aid of compression garments in reducing muscle oscillations (Kraemer et al, 1998; Mizuno et al, 2016), potentially through enhanced proprioceptive capability (Kraemer et al, 1998). However, there is currently no systematic study of the mechanisms underlying these acute changes in leg mechanical behavior wearing CS, and further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the acute increases in leg stiffness associated with a lower relative time spent in contact with the ground can be interpreted as a more dynamical running pattern and leg mechanical behavior. Previous studies have suggested such biomechanical improvements may reside in the ergogenic aid of compression garments in reducing muscle oscillations (Kraemer et al, 1998; Mizuno et al, 2016), potentially through enhanced proprioceptive capability (Kraemer et al, 1998). However, there is currently no systematic study of the mechanisms underlying these acute changes in leg mechanical behavior wearing CS, and further investigations are required.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after completing 60 min of each exercise, the subjects in the CG trial changed into a whole-body CG (Recharge; Under Armour, Baltimore, MD) [7, 24]. The pressure levels applied for the present CG were previously reported [25], 11.5 ± 0.6 hPa for thigh and 17.6 ± 1.8 hPa for calf. In the CON trial, the subjects wore a non-CG, identical type of sports wear without specific compression.…”
Section: Methodsmentioning
confidence: 99%
“…Power output for bench press power output during concentric phase (elevating phase) was determined using an accelerometer (Myotest SPORT, Myotest SA, Sion, Switzerland) connective to a bench press bar [25]. After the beep, the subjects completed bench press exercise during concentric (elevating) phase as fast as possible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, we used medical graduated compression stocking, which have also been used in some previous studies [25,26,27,28,29]. As evaluations, we measured Profile of Mood States (POMS), heart rate variability (HRV), and saliva stress-related markers.…”
Section: Introductionmentioning
confidence: 99%